2020
DOI: 10.1177/0194599820932541
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Eustachian Tube Dysfunction in the US Elderly Population

Abstract: Objective To investigate the prevalence of eustachian tube dysfunction (ETD) in elderly adults in the United States and its association with other upper aerodigestive inflammatory processes. Study Design Cross-sectional study. Setting Population based. Subjects and Methods In total, 147,805 patients without malignancy were compared to 13,804 demographically matched patients with malignancy of the upper aerodigestive tract (UADT) by querying the Surveillance, Epidemiology, and End Results (SEER)–Medicare linked… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 32 publications
(70 reference statements)
0
14
1
Order By: Relevance
“…In the USA, Shan et al [ 8 ] estimated that the overall prevalence of ETD among adults in was nearly 4.6%, consistent with a total of 11 million affected individuals. The prevalence was slightly higher among the elderly (5.4%) and among patients with malignancy (9.8%) [ 5 ]. A higher prevalence was estimated by Newman et al [ 9 ] who reported that the mean score of ETDQ-7 score for temporomandibular joint disorder patients was 24.5 ± 12.5.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the USA, Shan et al [ 8 ] estimated that the overall prevalence of ETD among adults in was nearly 4.6%, consistent with a total of 11 million affected individuals. The prevalence was slightly higher among the elderly (5.4%) and among patients with malignancy (9.8%) [ 5 ]. A higher prevalence was estimated by Newman et al [ 9 ] who reported that the mean score of ETDQ-7 score for temporomandibular joint disorder patients was 24.5 ± 12.5.…”
Section: Discussionmentioning
confidence: 99%
“…Also, it has long-term impacts, like communication difficulties and decreased productivity, which can contribute to low quality of life [ 2 ]. In adults, ETD can occur alone or in association with a variety of inflammatory illnesses of the aerodigestive tract [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Eustachian tube (ET) dysfunction (ETD) is estimated to account for over 2 million ambulatory visits in the United States each year with a prevalence ranging from 1% to 5%. [1][2][3] Although the past decade has seen growing interest in treatment of this condition, there have been few advances in refining the evaluation and diagnosis of ETD. 4 Some reports suggest that nasopharyngeal inflammation may be a contributing factor to ETD and has been associated with laryngopharyngeal reflux (LPR) and chronic rhinosinusitis (CRS).…”
mentioning
confidence: 99%
“…Eustachian tube (ET) dysfunction (ETD) is estimated to account for over 2 million ambulatory visits in the United States each year with a prevalence ranging from 1% to 5% 1–3 . Although the past decade has seen growing interest in treatment of this condition, there have been few advances in refining the evaluation and diagnosis of ETD 4 .…”
mentioning
confidence: 99%
“…E ustachian tube dysfunction (ETD) is a common entity affecting .4 million patients in the United States annually, with a limited but growing evidence base describing this condition. [1][2][3] Numerous treatment options have been proposed, but strong evidence is lacking to make definitive judgments on the most appropriate approach. [4][5][6][7] Impedance audiometry, also known as tympanometry, has been widely employed as an objective assessment of eustachian tube function, as reflected by the behavior of the tympanic membrane when subjected to brief changes in ambient pressure.…”
mentioning
confidence: 99%